2015
DOI: 10.2135/cropsci2014.05.0344
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs for Reproductive‐Stage Drought Resistance Traits using an Advanced Backcross Population in Upland Rice

Abstract: The reproductive stage of development is the most drought sensitive, and water deficits at that time can lead to a drastic yield reduction in rice (Oryza sativa L.). Understanding the genetic and physiological bases of yield and yield components under reproductive‐stage drought stress will help in the development of resilient cultivars. A population of backcross inbred lines derived from upland cultivars Apo and Moroberekan was used for mapping quantitative trait loci (QTLs) associated with grain yield and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…The drought tolerant landrace, Nootripathu flowered earlier than IR20 in all the trials. Similar results with drought tolerant landraces/donors flowering earlier than elite cultivars under drought were reported (Ghimire et al, 2012;Sellamuthu et al, 2015). The mean days to 50% flowering across RI lines was 99, 83, 76 and 73 in DS2012, DS2013, DS2014 and NS2014, respectively.…”
Section: Variation In Phenology and Plant Production Traitssupporting
confidence: 84%
See 1 more Smart Citation
“…The drought tolerant landrace, Nootripathu flowered earlier than IR20 in all the trials. Similar results with drought tolerant landraces/donors flowering earlier than elite cultivars under drought were reported (Ghimire et al, 2012;Sellamuthu et al, 2015). The mean days to 50% flowering across RI lines was 99, 83, 76 and 73 in DS2012, DS2013, DS2014 and NS2014, respectively.…”
Section: Variation In Phenology and Plant Production Traitssupporting
confidence: 84%
“…Hence this trial experienced severe reproductive stage drought. Reproductive stage drought stress is the most devastating in rice (Venuprasad et al, 2009;Sellamuthu et al, 2015). In DS2013, the rice lines were subjected to very severe drought stress since there was no rainfall right from emergence upto harvest and also lead to drying of bore well thus no irrigation could be provided.…”
Section: Drought Characterization Of Field Trialsmentioning
confidence: 99%
“…All other traits were associated at a significance level of 5%. Previous reports showed that RM514 flanks a QTLs linked to panicle length (Wang et al 2012), number of filled grains per panicle (Sellamuthu et al 2015), and grain yield, thousand-grain mass under water-stress conditions (Zou et al 2005). RM85, another marker on chromosome 3, was significantly associated with five traits, PN, E, Fv'/ Fm', ΦPSII, and ETR.…”
Section: Marker-trait Associationmentioning
confidence: 95%
“…It is more frequent in unbunded uplands, bunded uplands and shallow rainfed lowland fields as well as in many parts of South and Southeast Asia, sub-Saharan Africa and Latin America .In these regions the spatial and temporal variability of rainfall and coarsetextured soils in some parts exposes the rice plants to frequent drought spells. In subSahara African region it occupies about 9 million hectare which is about 84% of the total rice grown area while in Asia the total drought affected area is 23 million hectare (10 million hectare in upland and 13 million hectare in lowland, Pandey et al, 2005;Usman et al, 2013;Dixit et al, 2014;Kumar et al, 2014;Sellamuthu et al, 2015) with more than half across uplands and rainfed lowlands of India. The 2002 drought in India is described as one of the catastrophic event which reduced rice production by 17 million tons which is about 20% of the trend value (Pandey et al, 2007).…”
Section: Issn: 2319-7706 Volume 7 Number 05 (2018)mentioning
confidence: 99%